Flunixin Meglumine Is Superior to Meloxicam for Providing Analgesia after Surgical Castration in 2-Month-Old Goats - Victor Brusin; Maria Camila Ceballos; Pedro Henrique Esteves Trindade; Karen Camille Rocha Góis; Gabriel Conde; Virginia Tessarine Barbosa; Gustavo dos Santos Rosa; Mateus Jose Rodrigues Paranhos da Costa (Animals, 2022)
Farm animals are exposed to various painful procedures during their productive lives, making it necessary to implement anesthetic and analgesic protocols. However, there are few studies evaluating the effectiveness of these drugs. Our objective was to compare the analgesic effects of two nonsteroidal anti-inflammatory drugs (NSAIDs): meloxicam (MEL) and flunixin meglumine (FLU), in goat kids subjected to surgical castration under local anesthesia. Anglo-Nubian goat kids (60 days old) were allocated into two groups: MEL (n = 9), and FLU (n = 8), each administered 5 min before starting castration. All had been previously subjected to local anesthesia with lidocaine, injected bilaterally into the testes, plus subcutaneous in the scrotal raphe. Pain sensitivity was evaluated using the von Frey monofilaments test. Reactions were recorded before castration (M0), immediately after castration (M1), and once-daily for three consecutive days post-castration (M2, M3, and M4, respectively). Pain assessments were conducted in three body regions: at four points of the scrotum (dorsal and ventral; left and right lateral; R1); medial region of the pelvic limb, gracilis muscle (R2); and hypogastric region of the abdomen (R3). MEL goats had considerably greater pain reaction in R1 and R2 over time, mainly in M2; therefore, FLU was a more effective analgesic than MEL, resulting in less pain reaction.